2021
DOI: 10.3390/plants10071336
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anti-Inflammatory Effect of Moringa oleifera Lam. and Cyanthillium cinereum (Less) H. Rob. Lozenges in Volunteer Smokers

Abstract: Smokers have high plaque accumulation that initiates gingival inflammation and progresses to periodontitis. Thus, oral hygiene to control microbial plaque formation is an effective method of preventing gingivitis. Medicinal plants such as Moringa oleifera Lam. (MO) and Cyanthillium cinereum (Less.) H. Rob. (CC) have an anti-inflammatory effect that might improve oral health in smokers. This study evaluated the effect of MO leaf and CC extracts using MO lozenges and a combination of MO + CC lozenges on oral inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…A cross-over study including 20 subjects with mild to moderate gingivitis showed a greater reduction in mean gingival index scores and plaque scores with the MO-based dentifrice compared to a miswak-based dentifrice [47]. In addition, another study with MO leaf extract-based lozenges reduced inflammation and gingivitis in smokers [48]. In support of these findings, a model of periodontitis as a chronic inflammatory disease proved that MO leaf aqueous extract at 0.5 and 1 g/kg BW for 30 days provides anti-periodontitis activity in rats.…”
Section: Discussionmentioning
confidence: 98%
“…A cross-over study including 20 subjects with mild to moderate gingivitis showed a greater reduction in mean gingival index scores and plaque scores with the MO-based dentifrice compared to a miswak-based dentifrice [47]. In addition, another study with MO leaf extract-based lozenges reduced inflammation and gingivitis in smokers [48]. In support of these findings, a model of periodontitis as a chronic inflammatory disease proved that MO leaf aqueous extract at 0.5 and 1 g/kg BW for 30 days provides anti-periodontitis activity in rats.…”
Section: Discussionmentioning
confidence: 98%
“…For example, lupeol, gallic acid, and quercetin produced IC 50 values against DPPH activity of 30, 0.62, and 0.53 µg/mL, respectively [76,80]. Also, the leaf extract of V. cinerea exhibited antioxidant activity at 117.71 ± 15.02 µM Trolox equivalents/100 mg of dry extract [81].…”
Section: Antioxidant Activitymentioning
confidence: 97%
“…In addition, in smokers receiving three lozenges per day, an extract of the aerial parts of V. cinerea combined with a leaf extract of Moringa oleifera Lam. produced an antioral inflammatory effect, thus resulting in a 21.28% drop in the gingival index and a 57.14% decrease in oral inflammation [81].…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…Herbal lozenges composed of M. oleifera leaf and Cyanthillium cinereum (Less.) H. Rob extracts showed an antioxidant activity with powerful effects in reducing gingivitis and oral inflammation in a double-blinded, randomized, controlled clinical trial of smoker volunteers [ 43 ]. Mouthwashes containing ethanolic leaf extracts of Citrus hystrix , M. oleifera , and Azadirachta indica have been shown to decrease the gingival index and plaque index with a reduction in both Staphylococcus and Candida species in gingivitis subjects after 14 days in comparison with chlorhexidine gluconate [ 44 ].…”
Section: Effects Of Moringa In Oral Inflammatory C...mentioning
confidence: 99%